Increasing Students' Mathematics Ability Through Problem Based Learning - Fahmi Qodrul; M. Sameer Babu; Syarif Hidayat; Dian Indihadi (Journal of Future Education, 2023)
The capacity to apply, use, and interpret mathematics in various contexts is referred to as mathematical literacy. Examples of thiscapacity include the capacity to reason systematically and to describe or explain a phenomenon by predicting it using concepts, procedures and facts. One of the abilities students need to solve problems in real life is literacy. Therefore, research on how to develop and improve students' mathematical literacy skills is very important. This study aims to conduct a literature review on the topic of using PBL to improve students' mathematical literacy. SLR, or systematic literature review, is this research approach. Miscellaneous information is completed by reporting various articles linked to research studies. Through Google Schoolar searches, accredited national journals from sinta 1 to sinta 5 were included in this study. The study findings show that PBL can improve students' mathematical literacy. It also shows, based on published research, that PBL learning models can be developed or improved for teaching mathematics in schools.